Socio-political Longin Tsehel's'kyi during the First World War - Oksana Semyanyk (Cхід, 2013)
The article attempts to analyze aspects of social and political activity of one of the leading figures of Galician Longin Tsehel's'kyi. Considered his activities during World War I as inUkraineand abroad, participation in the political organizations of the period, analyzed its editorial and journalistic activities.